The Incorporation of Contractual Terms in Unsigned Documents – Is it Time for a Realistic, Consumer-Friendly Approach? - Webb, Eileen; Freilich, A. (University of Western Australia, 2009)
The common law relating to the incorporation of terms in standard form contracts has generaly failed to reflect the reality of the circumstances. Many of these transactions are consumer transactions. They should be classified as such and differentiated from commercial transactions. This classification should attract its own legal approach that utilises notions of the reasonable expectations of consumers, an effective and practical notice requirement as well as the concept of unfair contract terms. AS consumer law academics, we have always felt disquiet about the seeming powerlessness of consumers when certain terms, particularly exclusion clauses, are imposed upon them in unsigned documents. The law about the contractual status of such terms is that they are incorporated by reasonable notice1. The problem is determining just what constitutes reasonable notice and whether any such assessment is realistic, given the circumstances of the particular transaction. Indeed, in many commonly occurring transactions, it could be argued that the consumer does not receive any notice at all. In this article we will focus on the ticket scenario – where a document is handed to a person, very often after the payment of money, and that document contains the terms that govern the transaction. The article will examine the common law foundations of the ticket cases and then discuss the decision in eBay International AG v Creative Festival Entertainment Pty Ltd.2 In that case, Rares J held that the combined effect of two terms contained on the back of a ticket, in the circumstances of a consumer transaction, was misleading pursuant to section 52 of the Trade Practices Act 1974 (Cth).3 We will then propose that the e-Bay decision provides a more realistic approach to the ticket scenario and suggest that there should be a way to provide consumers with important information regarding the terms on the ticket, particularly where there are unusual terms or those which purport to place limitations on legal rights. We support our argument by reference to the traditionally differing approach to commercial and consumer transactions in the courts and to statutory initiatives, such as the Consumer Credit Code, which require the provision of certain information to consumers in an accessible, easy to understand form. The relevance of the proposed prohibition of unfair contract terms in the new Australian Consumer Law to ticket cases will also be discussed. The article concludes with a proposed disclosure document which could alert consumers to potential pitfalls when purchasing tickets. While the writers do not suggest such an innovation would be a panacea for all the difficulties associated with the law relevant to the sale of tickets and the subsequent enforcement of their terms, it would go some way towards addressing the imbalance between the seller and the consumer in such circumstances.